2014
DOI: 10.1111/den.12387
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between double‐guidewire technique and transpancreatic sphincterotomy technique for difficult biliary cannulation

Abstract: DWT and TPS procedures were safe and effective. Overall cannulation rate was similar between the groups. Although DWT had a longer cannulation time, it could be considered the preferred technique in patients with failed standard cannulation for lower adverse event rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…One hundred twenty‐four articles were judged not suitable for pooled analysis based on their abstracts. After vetting was complete, 69 articles were reviewed.…”
Section: Precut Sphincterotomy: Overview Of Clinical Results Since 2004mentioning
confidence: 99%
“…One hundred twenty‐four articles were judged not suitable for pooled analysis based on their abstracts. After vetting was complete, 69 articles were reviewed.…”
Section: Precut Sphincterotomy: Overview Of Clinical Results Since 2004mentioning
confidence: 99%
“…The literature predominantly reports outcomes from academic centres, where case mix and experience may differ from other settings. The included studies reported cannulation rates from 70.5 to 100%, 1743 with a median of 96% and mean of 91.4%. The consensus of the working party was that a competent ERCP practitioner should achieve a cannulation rate in excess of 90% with a target standard of 95% at expert centres.…”
Section: Domain: Completeness Of Proceduresmentioning
confidence: 99%
“…The studies were published from 2012 to 2020. Huang et al [18] published a retrospective study with a larger number of patients, but this was excluded by design to avoid bias.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%